Improving The Quality of Scientific Works Through the Use of Flipbook-Based Mendeley Guidelines for Students of Business Administration Department of Semarang State Polytechnic - Ana Putri Nastiti; Rifah Dwi Astuti; Sri Wahyuni; Sandi Supaya; Eva Purnamasari; Mellasanti Ayuwardani (Cita konsultindo, 2025)
Scientific work is a writing or research conducted as part of the academic tasks of academicians, including students. In the process of writing this scientific work, there is an unavoidable risk of plagiarism, whether intentional or unintentional. Writing quality scientific work requires the ability to select and compile a bibliography used as a reference, as well as skills in making accurate citations. Initial studies found that scientific work in the form of Final Projects and Theses produced by students of the Business Administration Department of Semarang State Polytechnic could not be said to be quality scientific work. The concept of a Flipbook-based Mendeley guidebook that the research team adopted in this study was considered to make it easier and more interesting for readers to use the book. The results of the study showed the highest increase of 49.1%, which indicates that the effectiveness of this guidebook has been proven to help students in implementing technical steps for writing citations that have an impact on improving the quality of scientific work.